The Strange Case of Dr Jekyll and Mr Hyde: A Graphic Novel in Full Colour - Grant, Alan, Stevenson, Robert Louis (Glasgow Waverly Books, 2017)
This acclaimed graphic novel from Alan Grant and Cam Kennedy is faithful to Stevenson's story, with great artwork from Cam Kennedy. When John Utterson notices that his friend, Dr Henry Jekyll, has been acting very strangely, he investigates and uncovers a terrifying and horrific story.